Pengaruh Model Pembelajaran Advance Organizer Berbantuan Media Interaktif Book Creator Terhadap Motivasi dan Hasil Belajar Fisika Siswa MA - Nala Fauziyah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine the effect of implementing the advance organizer learning model supported by the interactive Book Creator software on the motivation and physics learning outcomes of high school students regarding energy sources. A quantitative method was used. The use of the advance organizer learning model supported by the interactive Book Creator software can be utilized to measure students’ learning abilities. The research design used was a posttest-Only control group; this study can determine the effect on students’ motivation and physics learning outcomes. Data analysis utilized SPSS version 27 software with the Mann-Whitney U test. The analysis results indicate a significant effect between the average scores of the experimental class and the control class, with a test result of Asymp.Sig. 0.000 (< 0.05). Meanwhile, the learning outcomes showed an Asymp.Sig. value of 0.04 (< 0.05), indicating a significant effect between the average scores of the experimental and control classes. Therefore, it can be concluded that the implementation of the Advance Organizer learning model supported by the interactive Book Creator media has an effect on the motivation and physics learning outcomes of MA students.
:: Finalisasi file repositori 16 Juli 2026_Kurnadi
Keywords: Advance Organizer; Book Creator; Learning Motivation; Learning Outcomes